Djurskyddslagen och renskötseln - Pettersson, Hanna (2013)
The aim of this literature review was to discern which legislations and regulations related to animal welfare that comprises reindeer and their significance in reindeer husbandry. The Swedish Animal Welfare Act (1988:534) was enacted July 1, 1988 and its main purpose is to ensure a good animal health and environment. Animals that live in a good environment with good health is considered to have good welfare, which can be described as an individual's condition in relation to its surroundings. Reindeer herding is an extensive form without daily management. In reindeer husbandry there are eight specific seasons over the year and reindeer are handled as they migrates between pastures, get earmarks, are sorted for transport and slaughter. Functioning legislations and regulations are of great importance for both animals and stockmen. Reindeer husbandry is covered by the general legislations and regulations that exist and in addition to these, specific regulations control herding with helicopter, transport and slaughter. There are difficulties in interpreting the existing general laws and regulations and the specific regulations is somewhat inadequate whereupon further regulations regarding calf marking, herding with snowmobile and supplementary feeding would be beneficial. More research are needed on how different procedures actually affect the reindeer and how the new legislations can be formed. Syftet med denna litteraturstudie var att urskilja vilka lagar, förordningar och specifika föreskrifter gällande djurskydd som omfattar renar och vad de innebär för renskötseln. Djurskyddslagen (1988:534) stiftades den 1 juli 1988 och har som syfte att säkerställa en god djurhälsa och djurmiljö. Djur som lever i en god miljö med god hälsa anses ha en god välfärd, vilket kan beskrivas som en individs tillstånd i förhållande till dess omgivning. Renskötseln är idag en extensiv skötselform utan daglig hantering. Renåret kan delas in i åtta specifika perioder och under dessa perioder hanteras renarna när de drivs mellan beten, ...